1994
DOI: 10.1152/ajpendo.1994.266.1.e136
|View full text |Cite
|
Sign up to set email alerts
|

Ten days of exercise training reduces glucose production and utilization during moderate-intensity exercise

Abstract: We have previously shown that 12 wk of endurance training reduces the rate of glucose appearance (Ra) during submaximal exercise (Coggan, A. R., W. M. Kohrt, R. J. Spina, D. M. Bier, and J. O. Holloszy. J. Appl. Physiol. 68: 990-996, 1990). The purpose of the present study was to examine the time course of and relationship between training-induced alterations in glucose kinetics and endocrine responses during prolonged exercise. Accordingly, seven men were studied during 2 h of cycle ergometer exercise at appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 22 publications
9
48
2
1
Order By: Relevance
“…The resting glucose for the thirty-three swimmers ranged between 4.5 and 6.7 mmol/l with a mean of 5.5 ± 0.57 mmol/l, which is in line with that previously observed in a training population [15] (Table 1). …”
Section: Blood Glucose Response During the Incremental Swims Testsupporting
confidence: 90%
See 1 more Smart Citation
“…The resting glucose for the thirty-three swimmers ranged between 4.5 and 6.7 mmol/l with a mean of 5.5 ± 0.57 mmol/l, which is in line with that previously observed in a training population [15] (Table 1). …”
Section: Blood Glucose Response During the Incremental Swims Testsupporting
confidence: 90%
“…Following the occurrence of Gt (4.8 ± 0.39 mmol/l), there was a significant rise in blood glucose through the following stages of the test, reaching its maximum (7.1 ± 1.1 mmol/l) at the point of highest effort Gt universally occurred at a lower exercise-intensity than AnT. This observation is supported by data from other researchers [6,[15][16][17][18][19] who, although not directly identifying Gt, have suggested that factors other than the production of lactate influence carbohydrate metabolism prior to AnT. Irrespective of the method used to identify AnT (Borch, Cheng or Kindermann) and the method used to compare differences (glucose, lactate, heart rate or time), Gt occurred at between 6 and 10% lower intensity than at AnT.…”
Section: Discussionsupporting
confidence: 79%
“…During the trials, blood, expiratory gases, and skeletal muscle biopsies were taken. The short-term, 10-day training protocol has been effectively used to induce changes in exercise performance, metabolism, and muscle signaling in response to the same absolute intensity exercise by our group (2) and others (28,30).…”
Section: Experimental Design Of Exercise Trialsmentioning
confidence: 99%
“…b-receptors facilitate lipolysis during exercise through the stimulation of sympathetic nervous system activity, which counteracts circulating insulin action on adipocytes during prolonged exercise. 18,54 Stimulation of the sympathetic nervous system through the onset of exercise promotes the release of catecholamines-epinephrine and norepinephrine. The b 2 -receptor subtype is more effective under epinephrine exposure.…”
Section: Metabolic Systemmentioning
confidence: 99%